SAP Research RoofTop Marketplace - Hoyer, Volker; Gilles, Florian; Fleischmann, Kathrin; Dreiling, Alexander; Stanoevska-Slabeva, Katarina (My University, 2009)
Enterprise Mashups have gained momentum in the last years. Business users with no or limited programming skills are empowered to leverage in a collaborative manner existing mashable components. By combining and reusing Web-based resources within minutes, business users are able to create new value added applications to solve an individual and ad-hoc business problem. In this demo, we show the SAP Research RoofTop Marketplace prototype that transfers established marketplace concepts and principles to the Enterprise Mashup paradigm in order to handle business and organizational challenges of the Mashup paradigm in enterprise environments.